CARDIOLOGY AND NEUROLOGICAL DISEASES ASSOCIATED WITH PSYCHOLOGICAL FACTORS: A CLINICAL APPROACH - Mahsudov Valijon Gafurjonovich, (TADQIQOTLAR, 2026)
Abstract:  This  work  is  devoted  to  the  study  of  the  clinical  approach  to cardiological  and  neurological  diseases  associated  with  psychological  factors.  The study analyzes the impact of psychological states such as stress, anxiety, depression and emotional stress on the functioning of the cardiovascular and nervous systems. It is  shown  that  psychological  factors  play  an  important  role  in  the  development  of pathologies  such  as  arterial  hypertension,  ischemic  heart  disease,  arrhythmias, headaches, migraines and neuroses through psychosomatic mechanisms . The clinical approach emphasizes the need for a comprehensive assessment of patients, that is, a joint analysis of the somatic and psychological state. It also highlights the effectiveness of  early  diagnosis,  psychotherapeutic  approaches,  pharmacological  treatment  and preventive measures. In general, the integration of the areas of psychocardiology and neuropsychiatry is of great importance in modern medicine.